Improved Outcomes Found after Implementing a Systematic Evaluation and Program Improvement Process for Tuberculosis. (September 2013) - Cass, Anne; Shaw, Tambi; Ehman, Melissa; Young, Jan; Flood, Jennifer; Royce, Sarah
California's state and local tuberculosis (TB) programs collaborated to develop the Tuberculosis Indicators Project (TIP), a program evaluation and improvement process. In TIP, local and state staff review data, identify program gaps, implement plans to improve local TB program performance, and evaluate outcomes. After 10 years of project implementation, indicator performance changes and patient outcomes were measured. Eighty-seven percent of participating programs showed a performance increase in targeted indicators after three years compared with 57% of comparison groups. Statistically significant performance change was more common in the intervention local health departments (LHDs) than in comparison groups. The most notable performance changes were in the contact investigation and case management indicators. These results indicate that this systematic evaluation and program improvement project was associated with improved LHD TB control performance and may be useful to inform improvement projects in other public health programs.